Easy Interface and Control of Tele-education Robots - Yun, Sang-Seok; Kim, Munsang; Choi, Mun-Taek (SPRINGER, 2013)
In this paper, we propose a new form of teaching robot system for English classes, which utilizes a tele-operated robot controlled by a teacher from a remote site. By providing a unique operation interface that incorporates non-contact vision recognition technologies, a teacher can easily control the robot from a distance to provide lectures. A robot mechanism with a 3D facial avatar also makes it possible for dynamic behavior and movement controlled from a remote site. Due to the robot's ability to act in a human-like way, students show great interest and feel at ease learning English from the tele-operated robot. In a field pilot study, elementary students who participated have shown improvements on their standardized tests after the study, which means the tele-operated robot system could contribute effectively to educational systems, particularly in the area of English education.
Keywords: HEAD